Defiant - Sanderson, Brandon (New York : Delacorte Press, 2023)
Spensa needs all the knowledge she gathered in the Nowhere to end the Superiority's quest for galactic dominance, but first she must determine how far she is willing to go for victory.
Ages 12+
Keywords: Survival -- Juvenile fiction; Air pilots -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Young adult fiction; Science fiction